Lithium slag-based temperature-inhibiting anti-cracking waterproof agent and preparation method thereof
Through the lithium slag-based temperature-resistant cracking and waterproofing agent, the combination of modified lithium slag and temperature-resistant materials, the existing hydration temperature rise inhibitor is solved, and the temperature-resistant cracking and self-repairing functions of concrete are realized, and the durability and waterproofing performance of concrete are improved.
Patent Information
- Application Number
- CN202411844716.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
AI Technical Summary
The existing hydration temperature rise inhibitors are costly and have a retarding effect on concrete, which affects the construction progress and cannot self-repair cracks.
The lithium slag-based temperature-resistance and crack-resistant waterproofing agent is used. This agent consists of modified lithium slag, temperature-resistance materials, calcium ion compensator, complexing agent, precipitation components and temperature-change-induced fibers. By adsorbing the heat-resistance material through the porous structure of modified lithium slag, the concrete temperature shrinkage cracks are reduced, and insoluble crystals are generated through the synergistic action of calcium ion compensator and complexing agent to repair cracks.
It realizes the temperature-resistance and crack resistance of concrete, has the functions of compensating shrinkage and self-repair, and has excellent waterproofing effect, which reduces the risk of internal temperature increase and cracks in concrete, and improves the durability of concrete.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a lithium slag-based temperature-suppressing, crack-resistant and waterproof agent and a preparation method thereof, and belongs to the technical field of building materials such as cement and concrete. Background Art
[0002] In the early stage of pouring large-volume concrete, the heat released by cement hydration causes internal heat accumulation, temperature rises, and in the stage of temperature drop, when the temperature stress is greater than the tensile strength of concrete, cracks will appear, affecting the bearing capacity and durability of the structure. At the same time, many structures that are thinner than large-volume concrete, such as underground continuous walls, have faster surface heat dissipation. Under the influence of the temperature difference between the inside and outside of the concrete, the internal and external surfaces shrink inconsistently, thus generating stress. When the stress is greater than the tensile strength of the concrete at that time, the concrete will crack. Once the concrete structure cracks, it will further aggravate the migration of external corrosive media in the concrete.
[0003] The Chinese patent with publication number CN117326818A discloses a concrete hydration temperature rise inhibitor and its preparation method and application. The hydration temperature rise inhibitor includes the following raw materials by mass: 45-60 parts of temperature control component, 2-5 parts of setting adjustment component, 15-25 parts of early strength component, 3-8 parts of plasticizing component and 10-20 parts of compacting component. The Chinese patent with publication number CN115490453A discloses a slow-release concrete hydration temperature rise inhibitor and its preparation method and application. The hydration temperature rise inhibitor is composed of chitosan / alginate / acrylic copolymer composite gel and a retarder coated therein. This hydration temperature rise inhibitor slowly releases the coated retarder component, so that the content of the retarder component in the water phase in the early stage of cement hydration is less, the initial setting time is shortened, and when the cement is hydrated to a certain extent, the retarder component continues to be released to slow down the hydration rate, thereby achieving the purpose of reducing the hydration temperature rise, that is, regulation.
[0004] The above-mentioned hydration temperature rise inhibitors all have the problem of high cost. At the same time, they have a certain retarding effect on concrete, affecting the construction progress. They do not have the self-repairing performance for cracks that appear in the later stage. They can only "prevent cracks" but not "crack cure". Summary of the invention
[0005] In order to overcome the defects of the prior art, one of the objects of the present invention is to provide a lithium slag-based temperature-suppressing and anti-cracking waterproofing agent, which has good temperature-suppressing and anti-cracking performance, has the functions of compensating for shrinkage and self-repairing, and has excellent waterproofing effect.
[0006] The second object of the present invention is to provide a method for preparing a lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent.
[0007] To achieve the purpose of the present invention, the following technical solutions are provided.
[0008] A lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent, wherein the total mass of the raw material of the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent is 100%, wherein the components and their mass fractions are:
[0009]
[0010] Preferably, a lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent, taking the total mass of the raw material of the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent as 100%, wherein the various components and their mass fractions are:
[0011]
[0012] The modified lithium slag is prepared by the following method:
[0013] The lithium slag is put into a temperature-suppressing material melted at 90°C to 95°C, left for 1 day, and then dry-milled to obtain a powder, which is the modified lithium slag.
[0014] Lithium slag is usually industrial residue produced after lithium is extracted from lepidolite, spodumene and salt lake brine. The lithium slag described in the present invention is industrial residue produced by producing lithium carbonate by sulfuric acid method after calcining spodumene at a high temperature of 1000°C to 1200°C. Taking the total mass of lithium slag as 100%, sulfite ion (SO 3 2- ) is ≥15%; preferably SO 3 2- The mass fraction is 15% to 25%.
[0015] The temperature-suppressing material is a concrete hydration heat regulating material, which can be added to concrete to effectively reduce the peak value of cement hydration heat release and reduce the risk of concrete temperature shrinkage cracks. Preferably, the temperature-suppressing material includes octacosanol and triacontanol, and more preferably, the mass ratio of octacosanol to triacontanol is 1:1-3.
[0016] Preferably, based on the total mass of the lithium slag being 100%, the mass fraction of the temperature suppression material is 2% to 5%.
[0017] Preferably, the specific surface area of the modified lithium slag is 300m 2 / kg~450m 2 / kg.
[0018] The calcium ion compensator is one or more of calcium formate, calcium hydroxide, calcium nitrite and calcium dodecylbenzene sulfonate. Preferably, the calcium ion compensator comprises calcium formate and calcium hydroxide, and the mass ratio of calcium formate to calcium hydroxide is 1:5-15. The calcium formate content is ≥98%, the pH value (25°C) is 6.5-8.0, and the density is 2.02g / cm 3 ~2.03g / cm 3; Calcium hydroxide fineness ≥325 mesh, content ≥97%.
[0019] The complexing agent is one or more of ethylenediaminetetraacetic acid (EDTA), sodium citrate, thioglycolic acid and mercaptoethanol; preferably, the complexing agent includes ethylenediaminetetraacetic acid and sodium citrate, and the mass ratio of EDTA to sodium citrate is 1:0.1-0.3. EDTA is a white crystalline powder, with a content of ≥99% and a molecular weight of 292.24; sodium citrate is a white crystalline powder, with a content of ≥99% and a molecular weight of 294.10.
[0020] The precipitation component grows insoluble crystals by reacting with the calcium ion compensator, plugging the capillary pores and microcracks of the concrete matrix, thereby improving the waterproof and anti-seepage ability of the concrete. Preferably, the precipitation component is one or more of sodium carbonate, potassium carbonate and sodium bicarbonate; more preferably, the precipitation component is sodium carbonate carbon, with a fineness of ≥200 mesh, a content of ≥99%, and a molecular weight of 105.99.
[0021] Preferably, the mass ratio of the calcium ion compensator, the complexing agent and the precipitation component is 1:0.5-0.6:0.8-0.9.
[0022] The temperature change induced fiber is prepared by the following method:
[0023] The discarded masks without nose bars and ear hooks are mixed with hydrophilic materials, and then extruded into shapes after being melted at high temperature;
[0024] The extruded material is immersed in a cooling liquid for a period of time, taken out and dried to obtain the product; the cooling liquid is an organic solvent containing a temperature-sensitive material and a compound containing a silicon-oxygen group.
[0025] Preferably, before removing the nose piece and ear hooks from the discarded masks, they are first subjected to ultraviolet irradiation treatment, the wavelength of the ultraviolet irradiation is 200nm to 275nm, the time is 1h to 1.5h, the ambient humidity is controlled at 40% to 60%, and the ambient temperature is controlled at 20°C to 40°C.
[0026] Preferably, the mass ratio of the discarded mask without the nose piece and the ear hooks to the hydrophilic material is 95-98:5-2.
[0027] Preferably, the hydrophilic material is maleic anhydride grafted polypropylene and / or maleic anhydride grafted polyethylene; more preferably, the hydrophilic material is a mixture of maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene in a mass ratio of 1:0.5-1.
[0028] Preferably, the high temperature melting temperature is 175° C. to 190° C., and the high temperature melting time is 4 min to 5 min.
[0029] Preferably, the extrusion molding is specifically as follows: adding the high-temperature melted mixture into a screw extruder to extrude the raw silk, and then performing secondary stretching of the raw silk at 80° C. to 120° C., with each stretching multiple being 6 to 8 times;
[0030] Preferably, the diameter of the raw silk is 0.4 mm to 0.45 mm.
[0031] Preferably, the temperature-sensitive material is at least one of polyethylene, chlorinated polyethylene, chlorosulfonated polyethylene and cross-linked polyethylene;
[0032] And / or, the compound containing silicon oxygen groups is tetraethyl orthosilicate.
[0033] Preferably, in the coolant, based on the volume of the organic solvent, the content of the temperature-sensitive material is 200 g / L to 300 g / L, and the content of the silicon-oxygen group-containing compound is 100 g / L to 150 g / L.
[0034] More preferably, the temperature-induced fiber has a tensile strength greater than or equal to 500 MPa, an elastic modulus greater than or equal to 5 GPa, a length of 10 mm to 12 mm, and a diameter of 0.2 mm to 0.3 mm.
[0035] A method for preparing the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent according to the present invention, the method comprises the following steps:
[0036] The raw material components are weighed according to mass fraction and mixed evenly to obtain a lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent.
[0037] Beneficial Effects
[0038] (1) The present invention provides a lithium slag-based temperature-suppressing and anti-cracking waterproofing agent, which can specifically reduce concrete shrinkage cracks and reduce the temperature increase inside the concrete, thereby achieving self-repair of cracks during the concrete service stage.
[0039] (2) The present invention provides a lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent. The modified lithium slag used in the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent is obtained by adsorbing a molten temperature-suppressing material into a porous lithium slag. A large amount of temperature-suppressing material is stored in the porous structure of the modified lithium slag, which can reduce the influence of the lithium slag on the fluidity of the concrete mixture. At the same time, the temperature-suppressing material can achieve a cooling effect during the temperature rise stage of the concrete.
[0040] In addition, lithium slag contains sulfite ions (SO 3 2- ), during the concrete hardening stage, SO in lithium slag 3 2-It can promote the formation of insoluble crystalline calcium aluminate, causing the volume expansion of concrete, compensating for the shrinkage of concrete during the hardening stage, specifically reducing shrinkage cracks, and has a self-repairing function. 3 2- The mass fraction of is greater than or equal to 15%, which can ensure that there are enough sulfite ions to participate in the expansion reaction; further, in order to avoid excessive expansion and cracking caused by excessive sulfite ions, SO 3 2- The mass fraction of lithium slag should not exceed 25%; the volcanic ash effect of lithium slag can also be used to improve the density of concrete, thereby improving the durability of concrete.
[0041] (3) The present invention provides a lithium slag-based temperature-suppressing and anti-cracking waterproofing agent, in which temperature-change induced fibers are used. The temperature-change induced fibers are composite temperature-sensitive materials on the fiber surface. When the temperature generated during cement hydration is between 40°C and 90°C, the fibers can shrink as the temperature of concrete increases at 40°C to 90°C. The high temperature reduces the interaction force between the polyethylene molecular chains in the temperature-change induced fibers, and the highly oriented molecular chains are deoriented, resulting in increased thermal shrinkage performance. Under the condition of internal and external temperature difference, the fiber shrinks to reduce internal expansion, thereby reducing the internal surface stress gradient and achieving control of concrete cracks.
[0042] (4) The present invention provides a lithium slag-based temperature-suppressing and anti-cracking waterproofing agent, in which the calcium ion compensator, the complexing agent and the precipitation component can synergistically generate insoluble crystals, thereby improving the density of concrete and repairing cracks. When water enters the concrete through the cracks, the complexing agent and the Ca in the calcium ion compensator react with each other to form insoluble crystals. 2+ A complex reaction occurs to generate a water-soluble but unstable calcium complex. The calcium complex reacts with SO in the modified lithium slag. 3 2- , precipitation components and CO in concrete 3 2- , HCO 3 2- 、SiO 3 2- The replacement precipitation reaction occurs, generating insoluble precipitates, while repairing the cracks, the complexing agent is released and continues to be transported to the interior of the concrete and combined with Ca 2+ The complexation reaction is repeated to generate calcium complex, and the complexation-release-re-complexation-re-release reaction occurs continuously, so that the waterproofing agent has the function of self-repairing for a long time.
[0043] (5) The present invention provides a lithium slag-based temperature-suppressing and anti-cracking waterproofing agent, in which zirconium silicone can promote the hydration of unhydrated cement, promote the formation of calcium hydroxide, improve the density of concrete, and provide calcium ions for the formation of insoluble crystals; zirconium silicone can increase the reaction activity of lithium slag and improve the mechanical properties and expansion properties of concrete.
[0044] (6) The present invention provides a lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent, wherein the specific surface area of the modified lithium slag is preferably 300 m 2 / kg~450m 2 / kg, when the specific surface area is less than 300m 2 / kg, it has a greater negative impact on the working performance of the mixture. When the specific surface is greater than 450m 2 / kg, the internal pore structure is destroyed, which is not conducive to the adsorption of temperature-inhibiting materials. DETAILED DESCRIPTION
[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0046] In the following examples and comparative examples:
[0047] Lithium slag is the industrial residue produced by producing lithium carbonate using the sulfuric acid method after spodumene is calcined at a high temperature of 1000℃~1200℃;
[0048] The fineness of calcium hydroxide is 400 mesh;
[0049] The fineness of sodium carbonate is 230 mesh.
[0050] The temperature change induced fiber is prepared by the following method:
[0051] The discarded masks are first sterilized with ultraviolet light, the full plastic strip of the nose frame and the ear hooks are taken out, and the hydrophilic materials are mixed and then melted at high temperature. The temperature of the high temperature melting is 180°C, and the time of the high temperature melting is 4 minutes. After melting, the fibers are extruded and molded. After molding, the fibers are immersed in the cooling liquid for 1 minute, and then taken out and dried to obtain the temperature-induced fiber. The solvent of the cooling liquid is xylene, which contains 250g / L of the temperature-sensitive material and 100g / L of the siloxane group material, which are compounded to the fiber surface by impregnation;
[0052] The mixed hydrophilic material, wherein the mass ratio of the discarded mask to the hydrophilic material is 95:5, and the hydrophilic material is a mixture of maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene in a mass ratio of 1:1;
[0053] The temperature-sensitive material is chlorinated polyethylene;
[0054] The silicon oxygen group material is tetraethyl orthosilicate;
[0055] The extrusion molding is specifically as follows: adding the molten mask into a screw extruder, melt-extruding a raw wire with a diameter of 0.45 mm, and then performing secondary stretching on the raw wire, the stretching temperature is 100° C., and the stretching ratio is 6 times.
[0056] The discarded masks come from Quzhou Rongbo Biotechnology Co., Ltd.
[0057] The maleic anhydride grafted polypropylene is sourced from Shanghai Qiaowei Chemical Technology Co., Ltd.;
[0058] The maleic anhydride grafted polyethylene is sourced from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.
[0059] The temperature-sensitive material is from Yangzhou Tianshi New Material Technology Co., Ltd.
[0060] The tetraethyl orthosilicate is sourced from Zhangjiagang Xinya Chemical Co., Ltd.
[0061] Example 1
[0062] A lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent, wherein the total mass of the raw material of the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent is 100%, wherein the components and their mass fractions are:
[0063] Modified lithium slag 40%, calcium formate 3.8%, calcium hydroxide 19.2%, EDTA 10.5%, sodium citrate 2.1%, sodium carbonate 19.4%, silicone zirconium 2%, temperature change induced fiber 3%.
[0064] The modified lithium slag is prepared by the following method:
[0065] The lithium slag was put into the temperature-inhibiting material melted at 95°C, and after being left for 1 day, it was subjected to dry ball milling treatment for 5 minutes to obtain a specific surface area of 400m 2 / kg of powder is modified lithium slag.
[0066] The temperature-inhibiting materials are octacosanol and triacontanol in a mass ratio of 1:1.
[0067] Taking the total mass of lithium slag as 100%, the SO 3 2- The mass fraction of the thermal insulation material is 21%, and the mass fraction of the temperature suppression material is 3%.
[0068] The temperature-induced fiber has a tensile strength of 520 MPa, an elastic modulus of 5 GPa, a length of 12 mm, and a diameter of 0.2 mm.
[0069] A method for preparing the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent described in this embodiment, the method steps are as follows:
[0070] The raw material components are weighed according to mass fraction and mixed evenly to obtain a lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent.
[0071] Example 2
[0072] A lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent, wherein the total mass of the raw material of the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent is 100%, wherein the components and their mass fractions are:
[0073] Modified lithium slag 50%, calcium formate 3%, calcium hydroxide 15.1%, EDTA 7.9%, sodium citrate 1.6%, sodium carbonate 14.4%, silicone zirconium 4%, temperature change induced fiber 4%.
[0074] The modified lithium slag is prepared by the following method:
[0075] The lithium slag was put into the temperature-inhibiting material melted at 90°C, and after being left for 1 day, it was dry-milled for 5 minutes to obtain a specific surface area of 450m 2 / kg of powder is modified lithium slag.
[0076] The temperature-inhibiting materials are octacosanol and triacontanol in a mass ratio of 1:1.
[0077] Taking the total mass of lithium slag as 100%, the SO 3 2- The mass fraction of the thermal insulation material is 25%, and the mass fraction of the temperature suppression material is 5%.
[0078] The temperature-induced fiber has a tensile strength of 520 MPa, an elastic modulus of 5 GPa, a length of 10 mm, and a diameter of 0.24 mm.
[0079] A method for preparing the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent described in this embodiment, the method steps are as follows:
[0080] The raw material components are weighed according to mass fraction and mixed evenly to obtain a lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent.
[0081] Example 3
[0082] A lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent, wherein the total mass of the raw material of the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent is 100%, wherein the components and their mass fractions are:
[0083] Modified lithium slag 47%, calcium formate 1.2%, calcium hydroxide 16.9%, EDTA 8.3%, sodium citrate 2.4%, sodium carbonate 16.2%, silicone zirconium 1%, temperature change induced fiber 7%.
[0084] The modified lithium slag is prepared by the following method:
[0085] The lithium slag was put into the temperature-inhibiting material melted at 92°C, and after being left for 1 day, dry ball milling was performed for 5 minutes to obtain a specific surface area of 300m 2 / kg of powder is modified lithium slag.
[0086] The temperature-inhibiting materials are octacosanol and triacontanol in a mass ratio of 1:3.
[0087] Taking the total mass of lithium slag as 100%, the SO 3 2- The mass fraction of the thermal insulation material is 15%, and the mass fraction of the temperature suppression material is 2%.
[0088] The temperature-induced fiber has a tensile strength of 520 MPa, an elastic modulus of 5 GPa, a length of 11 mm, and a diameter of 0.3 mm.
[0089] A method for preparing the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent described in this embodiment, the method steps are as follows:
[0090] The raw material components are weighed according to mass fraction and mixed evenly to obtain a lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent.
[0091] Comparative Example 1
[0092] A lithium slag-based waterproofing agent, wherein the total mass of the lithium slag-based waterproofing agent raw material is 100%, wherein the components and their mass fractions are:
[0093] Lithium slag 40%, calcium formate 3.8%, calcium hydroxide 19.2%, EDTA 10.5%, sodium citrate 2.1%, sodium carbonate 19.4%, zirconium silicone 2%, temperature change induced fiber 3%.
[0094] The lithium slag was subjected to dry ball milling to obtain a specific surface area of 406 m 2 / kg of lithium slag.
[0095] Taking the total mass of lithium slag as 100%, the SO 3 2- The mass fraction is 21%.
[0096] The temperature-induced fiber has a tensile strength of 520 MPa, an elastic modulus of 5 GPa, a length of 12 mm, and a diameter of 0.2 mm.
[0097] A method for preparing the lithium slag-based waterproofing agent described in this comparative example, the method steps are as follows:
[0098] The raw material components are weighed according to mass fraction and mixed evenly to obtain a lithium slag-based waterproofing agent.
[0099] Comparative Example 2
[0100] A lithium slag-based waterproofing agent, wherein the total mass of the lithium slag-based waterproofing agent raw material is 100%, wherein the components and their mass fractions are:
[0101] Modified lithium slag 48%, calcium formate 1.2%, calcium hydroxide 16.9%, EDTA 8.3%, sodium citrate 2.4%, sodium carbonate 16.2%, temperature change induced fiber 7%.
[0102] The modified lithium slag is prepared by the following method:
[0103] The lithium slag was put into the temperature-inhibiting material melted at 95°C, and after being left for 1 day, dry ball milling was performed for 5 minutes to obtain a specific surface area of 405m 2 / kg of powder is modified lithium slag.
[0104] The temperature-inhibiting materials are octacosanol and triacontanol in a mass ratio of 1:3.
[0105] Taking the total mass of lithium slag as 100%, the SO 3 2- The mass fraction of the thermal insulation material is 21%, and the mass fraction of the temperature suppression material is 3%.
[0106] The temperature-induced fiber has a tensile strength of 520 MPa, an elastic modulus of 5 GPa, a length of 12 mm, and a diameter of 0.2 mm.
[0107] A method for preparing the lithium slag-based waterproofing agent described in this comparative example, the method steps are as follows:
[0108] The raw material components are weighed according to mass fraction and mixed evenly to obtain a lithium slag-based waterproofing agent.
[0109] Comparative Example 3
[0110] A lithium slag-based waterproofing agent, wherein the total mass of the lithium slag-based waterproofing agent raw material is 100%, wherein the components and their mass fractions are:
[0111] Modified lithium slag 43%, calcium formate 3.8%, calcium hydroxide 19.2%, EDTA 10.5%, sodium citrate 2.1%, sodium carbonate 19.4%, zirconium silicone 2%.
[0112] The modified lithium slag is prepared by the following method:
[0113] The lithium slag was put into the temperature-inhibiting material melted at 95°C, and after being left for 1 day, it was subjected to dry ball milling treatment for 5 minutes to obtain a specific surface area of 400m 2 / kg of powder is modified lithium slag.
[0114] The temperature-inhibiting material is octacosanol.
[0115] Taking the total mass of lithium slag as 100%, the SO 3 2- The mass fraction of the thermal insulation material is 21%, and the mass fraction of the temperature suppression material is 3%.
[0116] A method for preparing the lithium slag-based waterproofing agent described in this comparative example, the method steps are as follows:
[0117] The raw material components are weighed according to mass fraction and mixed evenly to obtain a lithium slag-based waterproofing agent.
[0118] Comparative Example 4
[0119] A lithium slag-based waterproofing agent, wherein the total mass of the lithium slag-based waterproofing agent raw material is 100%, wherein the components and their mass fractions are:
[0120] Modified lithium slag 40%, calcium formate 3.8%, calcium hydroxide 19.2%, EDTA 10.5%, sodium citrate 2.1%, sodium carbonate 19.4%, silicone zirconium 2%, temperature change induced fiber 3%.
[0121] The modified lithium slag is prepared by the following method:
[0122] The lithium slag was put into the temperature-inhibiting material melted at 95°C, and after being left for 1 day, it was subjected to dry ball milling treatment for 5 minutes to obtain a specific surface area of 400m 2 / kg of powder is modified lithium slag.
[0123] The temperature-inhibiting materials are octacosanol and triacontanol in a mass ratio of 1:1.
[0124] Taking the total mass of lithium slag as 100%, the SO 3 2- The mass fraction of the thermal insulation material is 8%, and the mass fraction of the temperature suppression material is 3%.
[0125] The temperature-induced fiber has a tensile strength of 520 MPa, an elastic modulus of 5 GPa, a length of 12 mm, and a diameter of 0.2 mm.
[0126] A method for preparing the lithium slag-based waterproofing agent described in this comparative example, the method steps are as follows:
[0127] The raw material components are weighed according to mass fraction and mixed evenly to obtain a lithium slag-based waterproofing agent.
[0128] Test experiment
[0129] (1) Temperature-induced fiber
[0130] The test specimens were molded according to the proportions in Table 1, and after demolding for 1 day, they were soaked in hot water at 75°C for 6 hours (special curing), and then taken out for standard curing for 7 days (standard curing temperature is 20°C, humidity is greater than 95%), and the tensile and bending properties were tested, and the number of fiber pullouts was counted and compared with the standard curing specimens at 20°C. The 1m long fiber was mounted on a scale and placed in a temperature matching curing room as a whole. The temperature was raised from the initial 40°C to 90°C at 5°C / hour, and the fiber deformation was calculated. The test results are shown in Table 2.
[0131] Table 1 Concrete mix ratio
[0132]
[0133] Table 2 Performance test results of temperature-induced fiber
[0134]
[0135] (2) Waterproofing agent
[0136] The waterproofing agents prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were added to the mortar in the form of internal mixing, replacing cement in equal amounts, with a mass fraction of 1%. The specific experimental group distribution ratios are shown in Table 3; the test pieces were molded according to the experimental group distribution ratios in Table 3, and the molds were removed after 1 day and placed in a standard curing room for curing. The crack self-repairing performance test method in TCECS913-2021 "Standard for Test Methods for Self-repairing Performance of Cement Concrete" was used to prefabricate cracks at the age of 7 days, and the crack self-repairing ability ratio at the age of 28 days was tested. The adiabatic temperature rise of concrete was tested according to DL / T 5150-2017 "Test Procedures for Hydraulic Concrete". The early crack resistance was tested according to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The shrinkage ratio at the age of 28 days was tested according to JC474-2008 "Mortar and Concrete Waterproofing Agent". The test results are shown in Table 4.
[0137] Table 3 Experimental group distribution ratio
[0138] Cement / g Standard sand / g Water / g Waterproofing agent / g 1336.5 4050 675 13.5
[0139] Table 4 Test results of embodiments and comparative examples
[0140] serial number Crack self-repairing ability ratio / % Adiabatic temperature rise / ℃ Number of cracks Shrinkage ratio / % Example 1 281 21 0 64 Example 2 285 18 0 58 Example 3 291 24 0 67 Comparative Example 1 270 32 1 71 Comparative Example 2 154 22 2 84 Comparative Example 3 273 25 4 66 Comparative Example 4 265 22 3 96
[0141] From the data in Table 4, it can be seen that in Comparative Example 1, since the lithium slag is not modified by temperature-suppressing material, the adiabatic temperature rise of the concrete is greatly increased; in Comparative Example 2, there is a lack of zirconium silicone, which cannot promote the hydration of unhydrated cement, thereby failing to promote the formation of calcium hydroxide to supplement calcium ions, failing to improve the self-repairing performance of concrete, and failing to promote the growth of the expansion product calcium aluminate, resulting in an increase in the shrinkage ratio; in Comparative Example 3, there is a lack of temperature-change induced fibers, which is manifested by an increase in the number of early cracks, and the temperature-suppressing material is a single octacosanol, resulting in an increase in the adiabatic temperature rise; in Comparative Example 4, the SO in the lithium slag 3 2- The mass fraction is only 8%, and the growth of the expanded product ettringite is reduced, which is manifested by an increase in the shrinkage ratio and an increase in the number of early cracks. 3 2- Different mass fractions of temperature-suppressing materials result in different shrinkage values and adiabatic temperature rises.
[0142] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent, characterized in that: Taking the total mass of the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent raw material as 100%, the various components and their mass fractions are: The modified lithium slag is prepared by the following method: The lithium slag is put into a temperature-suppressing material melted at 90°C to 95°C, and after being left for 1 day, dry ball milling is performed to obtain a powder, which is the modified lithium slag; Taking the total mass of lithium slag as 100%, the mass fraction of sulfite ion is ≥15%; The temperature-suppressing materials include octacosanol and triacontanol; The calcium ion compensator is one or more of calcium formate, calcium hydroxide, calcium nitrite and calcium dodecylbenzene sulfonate; The complexing agent is one or more of ethylenediaminetetraacetic acid, sodium citrate, thioglycolic acid and mercaptoethanol; The precipitation component is one or more of sodium carbonate, potassium carbonate and sodium bicarbonate; The temperature change induced fiber is prepared by the following method: The discarded masks without nose bars and ear hooks are mixed with hydrophilic materials, and then extruded into shapes after being melted at high temperature; The extruded material is immersed in a cooling liquid for a period of time, taken out and dried to obtain the product; the cooling liquid is an organic solvent containing a temperature-sensitive material and a compound containing a silicon-oxygen group.
2. A lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent according to claim 1, characterized in that: Taking the total mass of the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent raw material as 100%, the various components and their mass fractions are:
3. A lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent according to claim 1 or 2, characterized in that: The calcium ion compensator includes calcium formate and calcium hydroxide, and the mass ratio of calcium formate to calcium hydroxide is 1:5-15; The complexing agent comprises ethylenediaminetetraacetic acid and sodium citrate, and the mass ratio of ethylenediaminetetraacetic acid to sodium citrate is 1:0.1-0.3; The precipitated component is sodium carbonate carbon; The temperature change induced fiber has a tensile strength greater than or equal to 500 MPa, an elastic modulus greater than or equal to 5 GPa, a length of 10 mm to 12 mm, and a diameter of 0.2 mm to 0.3 mm.
4. A lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent according to claim 3, characterized in that: The mass ratio of the calcium ion compensator, the complexing agent and the precipitation component is 1:0.5-0.6:0.8-0.
9.
5. A lithium slag based temperature inhibiting, anti-cracking and waterproofing agent according to claim 1 or 2, characterized in that: Taking the total mass of lithium slag as 100%, SO3 2- The mass fraction is 15% to 25%.
6. A lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent according to claim 1 or 2, characterized in that: The temperature-suppressing material comprises octacosanol and triacontanol, and the mass ratio of octacosanol to triacontanol is 1:1-3.
7. A lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent according to claim 1 or 2, characterized in that: Taking the total mass of lithium slag as 100%, the mass fraction of the temperature suppression material is 2% to 5%.
8. A lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent according to claim 1 or 2, characterized in that: The specific surface area of the modified lithium slag is 300m 2 / kg~450m 2 / kg.
9. A method for preparing the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent according to any one of claims 1 to 8, comprising weighing the raw material components according to mass fraction, mixing them evenly, and obtaining the lithium slag-based temperature-suppressing, anti-cracking and waterproofing agent.
Citation Information
Patent Citations
Slow-release concrete hydration temperature rise inhibitor as well as preparation method and application thereof
CN115490453A
Concrete hydration temperature rise inhibitor as well as preparation method and application thereof
CN117326818A